Internal Battles: Examining How Anger/Hostility Moderate the Association Between Negative Urgency and Suicidal Desire Variables in Military and Civilian Samples. Issue 4 (6th February 2020) - Martin, Rachel L.; Bauer, Brian W.; Smith, Nicole S.; Daruwala, Samantha E.; Green, Bradley A.; Anestis, Michael D.; Capron, Daniel W.
Abstract: Objective: Suicide is consistently within the top ten leading causes of death in the United States. The suicide rate of National Guard personnel is elevated relative to the general population; however, research suggests that many of the suicide risk factors for military personnel are similar to the suicide risk factors for civilians. We examined whether negative urgency moderated the relationships between anger/hostility and perceived burdensomeness/thwarted belongingness in both a military and civilian samples. Method: There were two samples in the current study: (1) military personnel (majority national guard) and (2) community members oversampled for suicide attempt history. Results: Our hypotheses were partially supported with the interaction of hostility and negative urgency predicting perceived burdensomeness in the military sample. Within civilians, anger interacted with negative urgency to predict perceived burdensomeness. There were nonsignificant findings for analyses predicting thwarted belongingness. Exploratory analyses indicated that in both samples, anger and hostility interacted with negative urgency to predict suicidal ideation. Conclusions: Results suggest that aggressive attributes may contribute to individuals feeling as though they are a burden on others when moderate to high levels of negative urgency are present. Additionally, this study provides foundational support for the differences between suicidal desire and ideation.